2022
DOI: 10.1021/acsomega.2c02388
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Harmful Fly Ash Residue to Zeolites: Innovative Processes Focusing on Maximum Activation, Extraction, and Utilization of Aluminosilicate

Abstract: Reuse of the solid residue from coal fly ash alumina extraction (FAAE) by acid leaching is problematic. Conversion of this solid residue into aluminum-rich zeolite (13X) and silicon-rich zeolite (ZSM-5) was investigated in this research. The FAAE residue was activated by alkali roasting with Na 2 CO 3 powder (110% mass fraction) at 890 °C for 60 min. Silicon and aluminum were mainly present as two mineral phases, Na 2 SiO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Zeolite can activate antioxidant enzymes (peroxidase, catalase, and superoxide dismutase) (Huidong, 2022), which was reported in many animals. For example, dietary supplementation of rats with zeolite provided antioxidant protection after hepatectomy.…”
Section: Antioxidative Anti-inflammatory Effects Of Zeolitesmentioning
confidence: 77%
“…Zeolite can activate antioxidant enzymes (peroxidase, catalase, and superoxide dismutase) (Huidong, 2022), which was reported in many animals. For example, dietary supplementation of rats with zeolite provided antioxidant protection after hepatectomy.…”
Section: Antioxidative Anti-inflammatory Effects Of Zeolitesmentioning
confidence: 77%
“…Coal y ash was pretreated by calcination at 850ºC for 2 hours, to remove volatile materials present in the y ash and the unburned carbon. The calcination was followed by acid treatment in 20% HCl solution (10 ml HCl/g Ash) to dealuminate the y ash and remove iron for the activate the aluminosilicate minerals (Liu, 2022). The acid treated and calcined y ash was then mixed with NaOH at varying NaOH / y ash weight ratios (0.8 to 1.6) and fused in a stainless-steel tray at 550ºC for 1 h before it was cooled to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A promising technology that could complement HD for further and selective removal of sulfur compounds in petroleum fuels is adsorptive desulfurization (AD) by zeolite sorbent, which selectively removes sulfur compounds at ambient temperature and pressure without adsorbing aromatics and olefins present in the fuel [13][14][15]. Yang et al [9] found that zeolite sorbents usually bond with sulfur adsorbates via a ᴨ-complexation mechanism.…”
Section: Dr Januario Da Costa Hossimentioning
confidence: 99%
“…The influence of temperature and adsorbent's chemical composition on desulfurization performance was evaluated by varying the desulfurizing temperature (25-100 °C), zeolite Si:Al ratio (1, 2, and 3), and cationic exchanging the starting zeolite with Cu + , Ag + , and K + . To modify the Si:Al ratio, the starting zeolite material was contacted with a known amount of silica (Na 2 SiO 3 ) or alumina source (Al 2 (SO 4 ) 3 ), depending on whether more silicon or aluminum was required, in alkaline conditions with mild heating, followed by washing, filtration, and drying [13,14]. The cationic exchange was achieved by contacting the starting zeolite with an appropriate amount of aqueous AgNO 3 , CuSO 4 , and KCl to source Ag + , Cu 2+ , and K + cations, respectively.…”
Section: Adsorptive Desulfurization Proceduresmentioning
confidence: 99%